Calon Tunggal dalam Pemilihan Kepala Daerah dan Wakil Kepala Daerah Perspektif Hukum Progresif - Allan Fatchan Gani Wardana (Jurnal Hukum IUS QUIA IUSTUM, 2016)
Since its establishment until today, there have been many very progressive verdicts of Constitutional Court that can be used as the legal references for the acceleration of the legal reform in Indonesia. One of the verdicts of Constitutional Court is the one number 100/PUU-XIII/2015. This research is aimed to study the issues regarding first, whether the verdict of Constitutional Court Number 100/PUU-XIII/2015 on the single candidate in the election of the regional head and the deputy is included the progressive verdict? And second, what is the judicial implication of the Constitutional Court towards the nomination of the regional head and deputy? The research method used was the normative judicial method with the case approach. The results of the research concluded that first the verdict of the Constitutional Court Number 100/PUU-XIII/2015 is the progressive verdict. Second, the Verdict of the Constitutional Court has brought a judicial implication towards the nomination of the regional head and deputy that is by accommodating the single candidate in the implementation of the election of the regional head.